2018
DOI: 10.1093/annonc/mdx647
|View full text |Cite
|
Sign up to set email alerts
|

A predictive model of pathologic response based on tumor cellularity and tumor-infiltrating lymphocytes (CelTIL) in HER2-positive breast cancer treated with chemo-free dual HER2 blockade

Abstract: NCT01973660.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 11 publications
5
60
1
Order By: Relevance
“…Stromal tumor-infiltrating lymphocytes and tumor cellularity at C1D15 were independently associated with pCR. 22 The HER2-enriched intrinsic subtype (defined by PAM50) also was identified as a potential predictor of pCR. 20 In a study that investigated 12 weeks of lapatinib and trastuzumab, TBCRC006 investigators reported that activation of the phosphoinositide 3-kinase pathway is associated with resistance to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Stromal tumor-infiltrating lymphocytes and tumor cellularity at C1D15 were independently associated with pCR. 22 The HER2-enriched intrinsic subtype (defined by PAM50) also was identified as a potential predictor of pCR. 20 In a study that investigated 12 weeks of lapatinib and trastuzumab, TBCRC006 investigators reported that activation of the phosphoinositide 3-kinase pathway is associated with resistance to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous studies showing that TILs observed in breast cancers were associated with higher rate of pCR or improved overall survival outcomes [5,6]. Moreover, increasing TILs during systemic therapy was reported to be correlated with pCR [39], which suggests that MRI could provide valuable information regarding response during treatment.…”
Section: Luminal Subtypesupporting
confidence: 92%
“…None of the four major categories of change (proliferation, immune, stroma, and ERBB2 signaling) correlated with pCR ( Supplementary Figure 11), and in contrast to previous reports 53,54 as well as protein data from this cohort 52 , on-treatment immune infiltration, whether assessed using immune score or stromal TILs, was no more predictive than pre-treatment immune infiltration ( Supplementary Figure 12). There were also no differences in the changes in signatures by HR status (Supplementary Figure 13).…”
Section: Global Gene Expression Changes After Short-term Her2-targetecontrasting
confidence: 58%